An Analysis of Code-Mixing in Talk-show Bukan Empat Mata Program - Wardah A. M Daulay; Sumarsih Sumarsih (State University of Medan, 2012)
The paper examines the phenomena of using code-mixing on TV program, particularly in the talk-show Bukan Empat Mata within a multilingual communities, such as Indonesia. It looks at the different languages used in spoken and written forms. The purposes of this paper are to elaborate the theory, factors, types and the using of code-mixing. Key words: Code mixing